Annotation and the Ancient Greek Hero: Past, Present, and Future - Muellner, Lenny (My University, 2014)
My presentation will discuss the significance of annotation in the context of the highly successful HarvardX MOOC CB 22.1x The Ancient Greek Hero, which has been given twice, once in the spring of 2013, and once in the fall of 2013, and for which a third version is in preparation. I will discuss how annotation has been a source of knowledge about the interpretation of Homeric poetry, the primary vehicle for the study of the ancient Greek hero, since the death of Alexander the Great, and how the massive preservation of ancient annotations in medieval manuscripts of the Homeric _Iliad_ (including two at the Escorial in Madrid) and their digitization by a team of scholars and undergraduates is a vital educational project. More particularly, and in this same historical vein, I will discuss the way in which digital annotation has been a vital part of the HarvardX MOOC on the Ancient Greek Hero both as a tool for readers — becoming good readers of ancient texts is a central goal of this MOOC — and as a tool for self-assessment. I will also discuss how a new generation of federated annotation tools being developed by Daniel Cebrián Robles and Philip Desenne that feature tagging ontologies and the annotation of images promises to enhance the educational effectiveness of the next iteration of this MOOC.
Keywords: Enseñanza - Innovaciones tecnológicas; Mooc; Annotation mutimedia; Classical Studies